The Impact of Physical Activity During Pregnancy on Maternal and Fetal Outcomes: A Literature Review - Padula, Natalia; Pluszyński, Tomasz; Piotrowski, Karol; Jerczak, Małgorzata; Piórkowska, Iga; Polewka, Mikołaj; Polańska, Aleksandra; Paczosa, Kacper; Przybył, Filip (Quality in Sport, 2026)
Background. Physical activity during pregnancy is widely recognized as a key determinant of maternal and fetal health. Levels and patterns of physical activity often change across trimesters due to physiological, metabolic, and psychological adaptations. Given the dynamic nature of pregnancy, a comprehensive synthesis of current evidence on the effects and safety of physical activity across all trimesters is warranted to support trimester-specific recommendations and optimize maternal and neonatal outcomes. Aim. The aim of this review is to synthesize current evidence on physical activity throughout the entire course of pregnancy. Particular attention is given to trimester-specific patterns of physical activity, associated maternal and fetal health outcomes. Material and Methods A systematic literature review was conducted across international databases, encompassing meta-analyses, randomized controlled trials, cohort studies, and official guidelines from scientific societies. Key publications evaluating the physiological, biomechanical, and epigenetic effects of physical exertion were selected. Results. The accumulated evidence unequivocally demonstrates that regular physical exertion lowers the risk of gestational diabetes (by approx. 38%), pregnancy-induced hypertension (by approx. 58%), and fetal macrosomia, without negatively affecting the hemodynamic parameters of the umbilical artery. Studies from 2024-2025 confirm the safety of high-intensity training and submaximal resistance training. Furthermore, maternal exercise has been shown to have a stimulating effect on fetal epigenetic programming and neurogenesis, as well as a fundamental role of early mobilization in reducing symptoms of postpartum depression and pelvic floor dysfunction. Conclusion. Physical activity during pregnancy and the postpartum period is not only safe but constitutes a key prophylactic and therapeutic mechanism.